Da'wah management of the naqshbandiyah al-khalidiyah jalaliyah tharekat in recruiting jamaah - Rahmad Dian RizkI; Muhammad Habibi Siregar (Madania: Jurnal Ilmu-Ilmu Keislaman, 2026)
This study examines the implementation of Sufism-based da’wah management in the processes of member recruitment and development within an Islamic spiritual community. The study focuses on the conceptual framework of da’wah management, recruitment strategies, and the supporting as well as inhibiting factors influencing its implementation. The significance of this research lies in the limited number of studies that analyze Sufi communities from a managerial perspective, as previous research has predominantly concentrated on formal da’wah institutions. Furthermore, the challenges of modernity require systematic da’wah management without neglecting its spiritual dimensions. This research employs a qualitative approach using a field research method. Data were collected through in-depth interviews, participatory observation, and documentation, and were analyzed descriptively through the processes of data reduction, data display, and conclusion drawing. The findings reveal that the managerial functions of planning, organizing, implementing, and evaluating are applied contextually, although not formally structured within an administrative framework. Recruitment strategies are carried out through persuasive approaches, moral exemplification, spiritual education, and dhikr practices. This study recommends an integrative da’wah management model that combines modern management principles with Sufi values to enhance adaptability and sustainability.